2013
DOI: 10.3329/pa.v19i2.16949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E and Vitamin C on Mercury Induced Toxicity in Mice

Abstract: The present study was undertaken to find out the efficacy of vitamin E and/or vitamin C against mercury (Hg) induced toxicity in mice. Sixty mice were randomly divided into 5 equal groups (n=12). One group of mice (Group A) was kept as control and each of rest four groups (B, C, D and E) were fed with mercuric chloride (HgCl 2 ) in drinking water @ 65 mg/L. In addition to HgCl 2 alpha-tocopherol (vitamin E) @ 100 mg/L, ascorbic acid (vitamin C) @ 250 mg/L and combination of vitamin E and vitamin C at same dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…The effect of C. album is comparable with standard vitamin C group. Studies revealed that C. album contains vitamin C and E which play a vital role in hampering the absorption of Mercury in the gastrointestinal tract [11] and prevent ROS-mediated membrane damage by binding up ROS within the cell membrane [50]. It is postulated that the antioxidant CAT, SOD, and POD depletion by mercury may be a trigger for the production of reactive oxygen species (ROS) that induce lipid, protein, and DNA oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of C. album is comparable with standard vitamin C group. Studies revealed that C. album contains vitamin C and E which play a vital role in hampering the absorption of Mercury in the gastrointestinal tract [11] and prevent ROS-mediated membrane damage by binding up ROS within the cell membrane [50]. It is postulated that the antioxidant CAT, SOD, and POD depletion by mercury may be a trigger for the production of reactive oxygen species (ROS) that induce lipid, protein, and DNA oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Todos estos efectos tóxicos se redujeron en presencia de vitamina C (250 mg/) o vitamina E (100 mg/L), si bien la combinación de ambas fue el tratamiento más efectivo (Huq et al, 2008). La combinación de vitamina C y ácido fólico también mostró un efecto antagonista en embriones de pollo tratados con metilmercurio (2,5 mg), reduciendo en gran medida los efectos teratogénicos observados al inyectar la forma mercurial a los huevos fertilizados (Bekhet et al, 2013).…”
Section: Modulación Del Efecto Tóxico Del Mercurio Mediante La Dietaunclassified